2017
DOI: 10.1002/ijc.30579
|View full text |Cite
|
Sign up to set email alerts
|

Eurogin 2016 Roadmap: how HPV knowledge is changing screening practice

Abstract: Human papillomaviruses (HPVs) are the necessary cause of most cervical cancers, a large proportion of other anogenital cancers, and a subset of oropharyngeal cancers. The knowledge about HPV has led to development of novel HPV-based prevention strategies with important impact on clinical and public health practice. Two complementary reviews have been prepared following the 2015 Eurogin Conference to evaluate how knowledge about HPV is changing practice in HPV infection and disease control through vaccination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 95 publications
1
75
0
1
Order By: Relevance
“…HPV testing for cervical cancer screening is now a reality with several countries, either adopting this modality at the program level or introducing it through the execution of regional pilot studies . Support for this approach to screening is also endorsed by various professional societies and organizations which have global influence and reach .…”
Section: Active or Proposed Triage Policies For Hpv‐based Screeningmentioning
confidence: 99%
“…HPV testing for cervical cancer screening is now a reality with several countries, either adopting this modality at the program level or introducing it through the execution of regional pilot studies . Support for this approach to screening is also endorsed by various professional societies and organizations which have global influence and reach .…”
Section: Active or Proposed Triage Policies For Hpv‐based Screeningmentioning
confidence: 99%
“…Several countries are due to implement primary hrHPV testing with triage by cytology or, in some settings, partial genotyping 15 . Large randomised controlled trials have shown that hrHPV testing, when implemented over several rounds of screening, provided greater protection against CIN2+ or invasive cervical cancer than did cytological screening.…”
Section: Advances In Screeningmentioning
confidence: 99%
“…Even a single round of HPV testing can have a significant impact on the rate of advanced cervical cancers and cancer deaths in rural India 20 . Currently, the implementation of molecular testing in LMICs is limited because of cost and infrastructure requirements 15 . However, this might be addressed by using rapid low-cost point-of-care tests such as Xpert HPV, which has shown promise in a field trial in Papua New Guinea 21 .…”
Section: Advances In Screeningmentioning
confidence: 99%
“…There are now enough data to judge and guide the realistic clinical performance of multiple rounds of “cotesting” combining HPV testing with cytology. Second, young women vaccinated prophylactically against HPV have reached the age of screening, and HPV vaccination will increasingly and profoundly affect screening performance (8). Given the post-vaccination prevalence of precancer, cytology and pooled HPV tests perform less effectively (e.g., are less predictive of cervical precancer) in vaccinated populations than in unvaccinated populations.…”
mentioning
confidence: 99%